2020
DOI: 10.1017/s1047951120002425
|View full text |Cite
|
Sign up to set email alerts
|

QT interval evaluation associated with the use of hydroxychloroquine with combined use of azithromycin among hospitalised children positive for coronavirus disease 2019

Abstract: Introduction and aim: Hydroxychloroquine alone or in combination with azithromycin has been increasingly used for patients with COVID-19, in both children and adults. Drugs are generally well tolerated in clinical practice; however, both can cause corrected QT prolongation. We aimed to report our experience of QT interval evaluation associated with the use of hydroxychloroquine with concurrent azithromycin among children testing positive for COVID-19. Methods: Our single-centre; retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…The potential role of pharmacological treatments such as hydroxychloroquine (HCQ) and azithromycin in enhancing the susceptibility to QT-related life-threatening ventricular arrhythmias, particularly Torsades de pointes (TdP), is increasingly recognized in adults[ 147 - 149 ]. Nevertheless, pediatric observations have shown that these drugs are safe in previously healthy children[ 150 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential role of pharmacological treatments such as hydroxychloroquine (HCQ) and azithromycin in enhancing the susceptibility to QT-related life-threatening ventricular arrhythmias, particularly Torsades de pointes (TdP), is increasingly recognized in adults[ 147 - 149 ]. Nevertheless, pediatric observations have shown that these drugs are safe in previously healthy children[ 150 ].…”
Section: Resultsmentioning
confidence: 99%
“…Early in the pandemic, concerns have appeared about the potential of pro-arrhythmic events due to the use of prolonging-qt drugs that have raised, particularly the combined use of chloroquine (CQ), HCQ and azithromycin[ 147 - 149 , 191 , 192 ]. The authors of a small single-center, the retrospective study found no risk of QT prolongation or TdP in children with COVID-19 under treatment with HCQ[ 150 ]. However, the patients included were not severely affected by the disease, and none of them required intensive care, had cardiovascular comorbidity, and were taking corrected QT-prolonging medications, nor had ionic alterations.…”
Section: Resultsmentioning
confidence: 99%
“…Prolongation of the QTc interval can predispose patients to malignant ventricular arrhythmias including torsade de pointes [ 8 , 9 ]. In an effort to quantify the degree of QTc prolongation and the associated events of ventricular arrhythmias and torsade de pointes in patients with COVID-19 who were treated with hydroxychloroquine with and without azithromycin, multiple studies were published globally [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Our objective with this study was to systematically review the available literature, examining the association between the use of hydroxychloroquine with or without azithromycin in hospitalized patients with COVID-19 and QTc prolongation, as well as the incidence of ventricular arrhythmias and torsade de pointes.…”
Section: Introductionmentioning
confidence: 99%
“…No ECG abnormality was observed in any of our children who received azithromycin and chloroquine treatment. 25 Our study did not specify the treatments given to each patient individually, as the treatment guidelines frequently change according to new studies in our country and all over the world. Limitation of our study: it is a singlecenter and data for the beginning of the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%